LNG AFTER THE PANDEMIC - Tusiani, Michael D.; Shearer, Gordon (PennWell Books, 2023)
The world changed in 2020. An outbreak of Covid-19 turned into a worldwide pandemic followed by the Russian invasion of Ukraine just two years later. Two black swan events in the span of 24 months. LNG: After the Pandemic dives into the lessons learned from this unprecedented combination of events. Numerous trends are covered including volatile prices, the post-pandemic slump, increasing exports, the jump in European demand, and the pressures of decarbonization. This book considers the implications of these trends and sets the stage by looking at the fundamental changes in the industry that have occurred over the past decade. This new LNG landscape may help us discern where the industry's future lies. Despite the rhetoric, LNG is here to stay.